Investigation on a desiccant based solar water recuperator for generating water from atmospheric air. (2021) - Kumar, P. Manoj; Arunthathi, S.; Jeevan Prasanth, S.; Aswin, T.; Anish Antony, A.; Daniel, Deepak; Mohankumar, D.; Nikhil Babu, P.
Abstract: Drinking water scarcity becomes the alarming issue in recent days. On the other way, the atmospheric air carries a huge amount of water content in the form of water vapour. The suitable harvesting method can appositely address the water scarcity issue to a certain extent. This paper investigates a method of recovering potable water from the atmospheric air with the help of a desiccant based solar recuperation system. The orange silica gel was used as the desiccant by which the water molecules from the atmospheric air were adsorbed during the night time. The water from the laden silica gel was recuperated using a solar recuperation system during the day time. The experiments were conducted for three similar solar days during the month of April 2020 in Coimbatore, India, and the average results are presented. It was observed that the system produced 0.98 L of potable water per day, economically.